Free Exciton Spectra in Heteroepitaxial ZnSe/GaAs layers - RAKOVICH, YURY (American Physical Society, 2000)
The free-exciton photoluminescence (PL) and reflection spectra of metal-organic vapor-phase-epitaxy grown ZnSe/GaAs epilayers with a thickness greater than that of the strain relaxation thickness were studied experimentally and theoretically for temperatures in the range T=10?120 K. Calculations were performed in the framework of absorbing and reflecting dead layer models, using single and two-oscillator models, both including and neglecting spatial dispersion. The results rule out the explanation that the fine structure in the free-exciton PL spectra derives from thermal strain splitting and polariton effects, if this structure is not accompanied by a corresponding structure in reflection. It was shown that this structure in the PL spectrum originates mainly from light interference caused by the presence of a dead layer in the near-surface region, with the thickness of the dead layer depending on the excitation intensity. A correlation between the measured and inherent free-exciton spectra was established.
PUBLISHED
Keywords: Physics